Social Media Marketing, Brand Image dan Trust terhadap Repeat Purchase pada Marketplace - Harjuno Yumatri Utomo (Journal of Management and Bussines (JOMB), 2022)
The research aims to determine the effect of Social Media Marketing, Brand Image and Trust on Repeat Purchases. The research method used is a quantitative method by using a partial les square (PLS) in the analysis of the results. The sample in this study was 100 people who were obtained using a purposive sampling technique. This research data collection was carried out by distributing Google Forms. The results showed, Social Media Marketing (with a T-Statistic value of 4.088 > 1.96 (from table Zα = 0.05), Brand Image (with a T-Statistic value of 2.580 > 1.96 (from table Zα = 0.05), and Trust (with a T-Statistic value of 2.052 > 1.96 (from table Zα = 0.05) has a significantly positive effect on Repeat Purchases on the Bukalapak marketplace. Conclusions, Social Media Marketing, Brand Image and Trust affect Repeat Purchases on the Bukalapak marketplace.By creating the right Social Media Marketing strategy with the target audience, you can increase Brand Image and Trust values ​​that can influence Repeat Purchases on the Bukalapak marketplace. Keywords: Brand Image, Social Media Marketing, Trust